PROPUESTA PARA MEJORAR LA GESTIÓN DE ALMACENAMIENTO MEDIANTE LA METODOLOGÍA 5S EN EL DEPARTAMENTO DE LOGÍSTICA DE LA EMPRESA COSMO BELLEZA S.A. SANTO DOMINGO-ECUADOR - Solórzano Palacios, Lilibeth Mabely (2023)
This project was developed at Cosmo Belleza S.A, a beauty product importer, in which the current situation was analyzed using checklists with the aim of improving logistic and storage management, through the proposal of applying the 5S methodology to optimize resources and improve the work environment for employees. By identifying critical points in the logistics department, the most frequent problems were prioritized with the help of Ishikawa and Pareto diagrams. The frequency of problems that interfere with the process activities was analyzed, and it was considered that the problems that have the most impact on the work area are: lack of order and cleanliness in the area, incorrect management of expired products, inadequate warehouse distribution, unclassified tools, and excessive accumulation of products.